Structural, microstructural, ferroelectric and photoluminescent properties of praseodymium modified Ba0.98Ca0.02Zr0.02Ti0.98O3 ceramics. Issue 2 (1st February 2018) - Ramovatar,; Coondoo, Indrani; Satapathy, S.; Panwar, Neeraj
Abstract: The 'x' wt% (x = 0, 0.02, 0.04 and 0.06) Pr6 O11 modified Ba0.98 Ca0.02 Zr0.02 Ti0.98 O3 (BCZT – x Pr) piezoelectric ceramics have been fabricated by the solid state reaction method with sintering at 1450 °C (x = 0) and 1350 °C (0.02 ≤ x ≤ 0.06) for 2 h. The impact of Pr concentration on the structural, microstructural, photoluminescence and ferroelectric properties has been systematically investigated. The x-ray diffraction (XRD) patterns revealed the co-existence of tetragonal and orthorhombic phases at room temperature upto x = 0.04 Pr concentration. The grain size was found to decrease upto x = 0.04 Pr content. Room temperature Raman spectroscopy results were consistent with the XRD results. The photoluminescence (PL) spectra showed significant emissions consisting of strong blue (489 nm), green (528 nm) and red (649 nm) wavelengths. The emission intensities of PL spectrum were strongly Pr concentration dependent and a maximum value was obtained for 0.04 Pr modified BCZT ceramic. Further, a large remnant polarization (2Pr 13 µC/cm 2 ) and low coercive field (EC 22 V/cm) were obtained for BCZT – 0.04 Pr ceramic. The crystal structure and microstructure affect the photoluminescence and ferroelectric properties. Such properties of 0.04 Pr modified BCZT ceramic make it the potential candidate for novel integrated and multifunctional devices.